PENGARUH KEUNGGULAN BERSAING MELALUI KINERJA BISNIS (Studi Kasus Warung Makan Di Wilayah Tlogosari Semarang) - Prasidya Jati, Gilang Prasidya Jati; Sugiarto, Sugiarto (Faculty of Economics and Business Diponegoro University, 2015)
This research was conducted at the Public Eating In Semarang Tlogosari Regional Culinary Center . Data revenue at a food stall in 2013-2014 showed that the decrease in total revenues despite consumer food stalls Tlogosari Region increase every year . This study aimed to analyze whether there is connection between the diversity of products , quality products with business performance at a food stall in the area Tlogosari Semarang , and whether business performance diner Tlogosari Semarang can affect the competitive advantage of the food stalls in the area Tlogosari itself . The research sample 70 , the types and sources of data from the owner of the diner , method of data collection questionnaire distributed to respondents , as well as the methods of analysis used in this study multiple linear regression method . The results of this study , the effect of product diversity and quality of the products on competitive advantage that impact on business performance in the diner at the Culinary Center in Region Tlogosari . And advice in this research is variable product quality and product diversity is a good variable to increase competitive advantage .